Curve-based image editing for product styling. Issue 3 (4th May 2018) - Wang, Bo; Li, Bao-Jun; Giannini, Franca; Monti, Marina; Hu, Ping; Liang, Ji-Cai
ABSTRACT: This paper presents an approach for curve driven image warping to reshape the content of an image. The warping method is realized by inverse irregular quad mesh mapping. Considering that stylists adopt a curve based approach for their product shape definition, the devised curve driven image warping can provide a good mean for rapidly changing the product shape, thus easing the evaluation of shape alternatives. Moreover, here we show that the semantically editing of automotive images can be easily implemented combining this method with the automatic identification of the semantically important character lines. GRAPHICAL ABSTRACT: